Polyglycolic acid as well as preparation method and application thereof

By polymerizing and solid-phase tackifying in the presence of a catalyst, the problems of low molecular weight and complex process of polyglycolic acid are solved, and the efficient preparation of polyglycolic acid with low melt flow rate is achieved, meeting the needs of blowing film and blow molding and simplifying the process , improves product performance.

CN119264393APending Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310820301.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the prior art, polyglycolic acid has low molecular weight and large melt flow rate, which is difficult to meet the application needs of low melt flow rate such as blowing films and blow molding. The traditional preparation process is complex, the equipment investment is large, and the area is large. , and there are problems of insufficient product performance caused by uneven molecular weight and excessive viscosity.

Method used

Polyglycolic acid precursors were obtained by polymerizing a mixture containing glycolic acid monomer and polyhydroxy polymer in the presence of a catalyst, and under solid-phase tackification conditions (time is 0.5 to 12 hours, temperature is 120 to 210°C , the absolute vacuum degree is not greater than 1000 Pa) and solid phase viscosity is increased to obtain polyglycolic acid with a specific melt flow rate ratio.

Benefits of technology

It realizes the obtaining of polyglycolic acid with low melt flow rate in a short time, meets the application needs of blown films, blow molding, etc., simplifies the process, reduces equipment requirements, improves production efficiency, and improves the performance and molecular weight of the product. Uniformity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264393A_ABST
    Figure CN119264393A_ABST
Patent Text Reader

Abstract

The invention relates to the field of polymers, and discloses polyglycolic acid and a preparation method and application thereof, and the polyglycolic acid contains a structural unit a from a polyhydroxy polymer. MFR1230 DEG C / 2.16 kg and MFR2230 DEG C / 2.16 kg represent the melt flow rates of the polyglycolic acid before solid phase tackifying and before and after solid phase tackifying at 230 DEG C and 2.16 kg respectively, the ratio of the MFR1230 DEG C / 2.16 kg to the MFR2230 DEG C / 2.16 kg of the polyglycolic acid is not less than 1.3, and the melt flow rate MFR2230 DEG C / 2.16 kg is not greater than 15 g / 10 min. The polyglycolic acid provided by the invention can better meet the application requirements of film blowing, blow molding and the like requiring low melt flow rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymers, and in particular to polyglycolic acid and a preparation method and application thereof. Background Art

[0002] Polyglycolic acid (PGA) is a completely biodegradable material. Due to its excellent mechanical properties, biocompatibility, biodegradability and gas barrier properties, it can be used in many fields such as surgical sutures, barrier materials, temporary plugging materials and disposable packaging bags. Generally, the higher the molecular weight of the polymer, not only will the mechanical properties be improved, but the melt flow rate (also known as melt index) will also decrease, which can better meet the application requirements of blown film, blow molding and other applications that require a low melt flow rate.

[0003] Generally, only low molecular weight PGA can be obtained from monomer polycondensation, while high molecular weight PGA can only be obtained through ring-opening polymerization of glycolide. However, the traditional preparation of high molecular weight and low melt flow rate PGA still requires a long reaction time, so most of them are batch reactions.

[0004] CN1930211B (Kureha Co., Ltd.) discloses a method for producing aliphatic polyesters with less residual cyclic esters; the main process of this method is: when aliphatic polyesters are produced by ring-opening polymerization of cyclic esters, at least in the later stage of polymerization, the polymerization is carried out in the form of solid phase polymerization, and the generated aliphatic polyester is supplied to the process of removing the residual cyclic esters from the gas phase. In addition, the polymerization process in this technology is a low-temperature intermittent autoclave reaction, the polymerization reaction temperature is lower than 195°C, and the reaction time is relatively long (the typical polymerization reaction time is 7 hours). More importantly, the patent only mentions reducing residual monomers, and does not mention increasing molecular weight or viscosity.

[0005] CN106928437B (Shanghai Pujing Chemical Technology Co., Ltd.) discloses a device and process for preparing high molecular weight polyester by ring-opening polymerization of cyclic esters. The process mainly comprises: preheating and melting the raw materials cyclic ester, catalyst and initiator respectively, adding them to a static mixer for prepolymerization, and then sending them to a reaction fluidized bed for atomization and reacting under an inert carrier gas. The obtained polyglycolic acid powder is sent to a solid phase thickening fluidized bed for thickening reaction, and finally sent to a bag filter for separation to obtain the product, which is a high molecular weight polyester. This process has the following defects: first, the process flow is relatively long, the equipment investment is large, and the floor space is also large; second, in this process, PGA is in powder form during solid-phase thickening, and each powder particle is independent and there is no material exchange between each other, that is, a single particle is a reaction system, so it is necessary to ensure that all reaction elements are complete in each particle for solid-phase thickening reaction to occur, and the smaller the particle size, the more difficult it is to have all reaction elements complete, and even with premixing and prepolymerization, it is still difficult to ensure uniform dispersion; finally, since the prepolymer needs to be atomized before thickening, and when the prepolymer viscosity is too high, it will be difficult to atomize evenly, so the prepolymer viscosity must be low and the molecular weight is also low, and it cannot be used directly.

[0006] CN114075332A (National Energy Investment Group Co., Ltd.) discloses a modified polyglycolic acid and its preparation method and application, which has the characteristics of high weight average molecular weight, high melt viscosity and low melt flow rate. However, the modification method is to add isocyanate after obtaining polyglycolic acid, which belongs to post-processing modification, and needs to react in the molten state of PGA, and the blending temperature is above 220°C, which does not belong to the category of solid phase viscosity enhancement. However, PGA has poor thermal stability, and conventional ring-opening catalysts are also ester exchange catalysts. Therefore, when reacting at a higher temperature, there will be more obvious ester exchange reactions, and the molecular weight will be more easily reduced. In addition, isocyanate is highly toxic and has a certain impact on operators and the environment during manufacturing and subsequent use. Summary of the invention

[0007] The purpose of the present invention is to overcome the problem in the prior art that polyglycolic acid (PGA) has a low molecular weight and a large melt flow rate, and is difficult to meet the application requirements of film blowing, blow molding, etc. that require a low melt flow rate.

[0008] In the study of polyglycolic acid, the applicant found that by selecting the characteristics of the melt flow rate (MFR) in polyglycolic acid, it can be better used in applications requiring a low melt flow rate, such as blown film and blow molding. The melt flow rate (MFR) of the polyglycolic acid can be obtained by a certain degree of viscosification of the starting polymer, preferably solid phase viscosification.

[0009] Based on the above findings, the applicant of the present application first proposes a polyglycolic acid different from the prior art, wherein the polyglycolic acid contains a structural unit a derived from a polyhydroxy polymer; the polyglycolic acid has a melt flow rate MFR2 230℃ / 2.16kg Not more than 15g / 10min; Melt flow rate MFR1 of polyglycolic acid before and after solid phase viscosity enhancement 230℃ / 2.16kg / MFR2 230℃ / 2.16kg The ratio is not less than 1.3; MFR1 230℃ / 2.16kg and MFR2 230℃ / 2.16kg They represent the melt flow rates of polyglycolic acid before and after solid phase thickening when tested at 230°C and 2.16 kg.

[0010] The applicant has found in research that polyglycolic acid with specific characteristics can be obtained by controlling the process of solid phase thickening. The second aspect of the present invention provides a method for preparing polyglycolic acid, which comprises: (1) in the presence of a catalyst, a mixture A comprising a glycolic acid monomer and a polyhydroxy polymer is subjected to a step of polymerization to obtain a polyglycolic acid precursor; (2) a mixture B comprising a polyglycolic acid precursor is subjected to solid phase thickening to obtain the polyglycolic acid; wherein the melt flow rate MFR1 of the polyglycolic acid precursor is 230℃ / 2.16kg / MFR2 230℃ / 2.16kg The ratio is not less than 1.3; the conditions for solid phase viscosity enhancement include: the time is 0.5 to 12 hours.

[0011] The third aspect of the present invention provides use of the polyglycolic acid of the present invention in blown film products and / or blow molded products.

[0012] Compared with the prior art, the present invention has at least the following advantages: the polyglycolic acid of the present invention can better meet the application requirements of blown film, blow molding, etc. that require a low melt flow rate, and its preparation process is relatively simple, the equipment requirements are relatively low, the production efficiency is high, and polyglycolic acid with a low melt flow rate can be obtained in a shorter time. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 GPC curves of some examples (Examples 1-3) and comparative examples (Comparative Examples 1-2);

[0014] Figure 2 The influence curves of the number average molecular weight and weight average molecular weight of the high molecular weight portion of polyglycolic acid during the solid phase viscosity enhancement and devolatilization process in Examples 1-3;

[0015] Figure 3 The influence curve of the number average molecular weight and weight average molecular weight of the medium and low molecular weight parts of polyglycolic acid in the process of solid phase viscosity enhancement and devolatilization in Examples 1-3;

[0016] Figure 4This is the influence curve of the proportion of high molecular weight components in polyglycolic acid during the solid phase viscosity increasing and devolatilization process in Examples 1-3. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] The starting material for preparing polymers is the polymerizable monomer. When preparing existing polymers, there are often monomers remaining in the corresponding polymers. Due to the complexity of the polymerization process, the prepared polymers are composed of different molecular weights, including some polymers sold on the market. They also have the above characteristics. It can be understood that the polyglycolic acid in the present invention also has the above characteristics.

[0019] The first aspect of the present invention provides a polyglycolic acid, which also has a structural unit a derived from a polyhydroxy polymer; the polyglycolic acid has a melt flow rate MFR2 230℃ / 2.16kg Not more than 15g / 10min; Melt flow rate MFR1 of polyglycolic acid before and after solid phase viscosity enhancement 230℃ / 2.16kg / MFR2 230℃ / 2.16kg The ratio is not less than 1.3; MFR1 230℃ / 2.16kg and MFR2 230℃ / 2.16kg They represent the melt flow rates of polyglycolic acid before and after solid phase thickening when tested at 230°C and 2.16 kg.

[0020] In the present invention, the characteristics of the melt flow rate (MFR) of polyglycolic acid are selected so that it can be better used in applications requiring a low melt flow rate, such as blown film and blow molding.

[0021] According to the present invention, in some embodiments, MFR2 230℃ / 2.16kg No more than 15g / 10min, for example, 0.1g / 10min, 0.5g / 10min, 1g / 10min, 2g / 10min, 3g / 10min, 4g / 10min, 5g / 10min, 10g / 10min or 15g / 10min, and a range consisting of any two of the above values, preferably no more than 10g / 10min, more preferably 0.5 to 5.0g / 10min. With the above embodiment, the polyglycolic acid of the present invention can better meet the application requirements of low melt flow rate such as film blowing and blow molding.

[0022] According to the present invention, in some embodiments, MFR1 230℃ / 2.16kg / MFR2 230℃ / 2.16kg The ratio is not less than 1.5, preferably 3.0 to 6.0. With the above-mentioned embodiment, the polyglycolic acid of the present invention can better meet the application requirements of film blowing, blow molding and the like which require a low melt flow rate.

[0023] According to the present invention, in some embodiments, MFR1 230℃ / 2.16kg The melt flow rate of the polyglycolic acid of the present invention is 3 to 60 g / 10 min, for example, 3 g / 10 min, 5 g / 10 min, 10 g / 10 min, 15 g / 10 min, 20 g / 10 min, 30 g / 10 min, 40 g / 10 min, 50 g / 10 min or 60 g / 10 min, and the range of any two of the above values, preferably 10 to 40 g / 10 min. With the above embodiment, the polyglycolic acid of the present invention can better meet the application requirements of film blowing, blow molding and the like requiring a low melt flow rate.

[0024] In the present invention, according to ISO 1133 standard, the CEAST MF20 melt flow rate tester of Instron Company is used for testing, the barrel temperature is 230°C, the weight load is 2.16kg, the die diameter is 2.095mm, the length is 8mm, the preheating time is 4min, and the sample is automatically cut every set time. The average value is taken 5 times, and the measurement result is expressed in grams per 10 minutes (g / 10min).

[0025] According to the present invention, in some preferred embodiments, the average number of hydroxyl groups on a single molecular chain of the polyhydroxy polymer is not less than 8, preferably not less than 20, and preferably 100 to 2000. The polyglycolic acid of the aforementioned embodiment can better meet the application requirements of blown film, blow molding, etc. that require a low melt flow rate, and the prepared product has better performance.

[0026] According to the present invention, in some more preferred embodiments, the number average molecular weight of the polyhydroxy polymer is not less than 3000 g / mol, preferably not less than 10,000 g / mol, and more preferably 30,000 g / mol to 300,000 g / mol. The polyglycolic acid of the aforementioned embodiment can better meet the application requirements of film blowing, blow molding, etc. that require a low melt flow rate, and the prepared product has better performance.

[0027] According to the present invention, in some more preferred embodiments, the polyhydroxy polymer includes at least one of polysaccharides and their derivatives, multi-arm polyethylene oxide, multi-arm polypropylene oxide, multi-arm polyethylene glycol, polyvinyl alcohol and its derivatives, preferably polyvinyl alcohol and / or ethylene-vinyl alcohol copolymer. The polyglycolic acid of the aforementioned embodiment can better meet the application requirements of low melt flow rate such as film blowing and blow molding, and the prepared product has better performance.

[0028] According to the present invention, in some particularly preferred embodiments, the structure of the structural unit a is as shown in formula (I):

[0029]

[0030] In formula (I), x, y and z all represent the degree of polymerization, the sum of x, y and z is not less than 50, preferably 50-6000, more preferably 200-2500; and / or, the proportion of z to the sum of x+y+z is 0%-50%; and / or, the proportion of x to the sum of x+y is 0%-32%.

[0031] According to the present invention, in some embodiments, the residual monomer content in the polyglycolic acid is not higher than 3.5% by mass, preferably 0.1% to 2.5%. The polyglycolic acid in the above embodiment can better meet the application requirements of film blowing, blow molding, etc. that require a low melt flow rate.

[0032] In the present invention, the residual monomer content test method of the sample is: about 0.04g of sample is dissolved in about 50g of dimethyl sulfoxide, heated at 160°C until the sample is dissolved, cooled to room temperature, centrifuged and filtered, 1.5μL of the solution is measured, and injected into a gas chromatograph for measurement. The numerical value obtained by the measurement is used to calculate the residual monomer content in the form of polymer total content%. Gas chromatography (GC) analysis is carried out on Agilent's GC7890 gas chromatograph; the detector is FID; the temperature of the injection port and the detector is 300°C; the chromatographic column is DB-FFAP 30m; the vaporization chamber temperature is 200°C; the chromatographic column temperature: the initial temperature is 160°C, and it is increased to 220°C at a rate of 10°C per minute and maintained for 4.5 minutes.

[0033] According to the present invention, in some embodiments, the total weight average molecular weight of the polyglycolic acid is 200,000 to 600,000 g / mol. The polyglycolic acid in the above embodiments can better meet the application requirements of film blowing, blow molding, etc. that require a low melt flow rate.

[0034] According to the present invention, in some preferred embodiments, the polyglycolic acid comprises a low molecular weight portion and a high molecular weight portion, and preferably the mass ratio of the high molecular weight portion to the low molecular weight portion is 1:200 to 3:2, for example, 1:200, 1:120, 1:100, 2:98, 5:95, 8:92, 12:88, 40:60, 50:50, 60:40, or a range consisting of any two of the above ratios, preferably 2:98 to 60:40. The polyglycolic acid under the aforementioned embodiment can better meet the application requirements of low melt flow rate such as film blowing and blow molding.

[0035] The polyglycolic acid of the low molecular weight portion and the high molecular weight portion described in the present invention does not include residual monomer content.

[0036] According to the present invention, in some more preferred embodiments, the weight average molecular weight of the high molecular weight portion of the polyglycolic acid is greater than 500,000 g / mol, preferably 2.5 million g / mol to 4 million g / mol. The polyglycolic acid in the aforementioned embodiment can better meet the application requirements of blown film, blow molding, etc. that require a low melt flow rate.

[0037] According to the present invention, in some more preferred embodiments, the weight average molecular weight of the low molecular weight portion of the polyglycolic acid is 150,000 to 300,000 g / mol. The polyglycolic acid in the aforementioned embodiment can better meet the application requirements of blown film, blow molding, etc. that require a low melt flow rate.

[0038] According to the present invention, in some more preferred embodiments, the content of oligomers with a weight average molecular weight of less than 1000 g / mol in the polyglycolic acid is less than 0.5% by mass. The polyglycolic acid in the above embodiments can better meet the application requirements of blown film, blow molding, etc. that require a low melt flow rate.

[0039] In the present invention, the molecular weight of polyglycolic acid is detected by gel permeation chromatography (GPC). The specific detection method can adopt conventional detection parameters in the art. For example, but not limited to, the following method is used: the test instrument is a PL-GPC50 gel permeation chromatograph of Angilent, USA, and the processing software is GPC offline. During the test, the mobile phase is hexafluoroisopropanol containing 5mmol / L sodium trifluoroacetate, the flow rate is 1mL / min, the column temperature is 40°C, the injection volume is 100μL, the standard sample is PMMA, and the sample concentration is 1mg / mL. According to the analytical method known in the art, the specific values ​​of the above parameters are obtained.

[0040] According to the present invention, in some embodiments, the high molecular weight portion is a polyglycolic acid graft copolymer.

[0041] According to the present invention, in some preferred embodiments, the polyglycolic acid graft copolymer contains structural unit a and structural unit b derived from glycolic acid monomer. The polyglycolic acid of the aforementioned embodiment has more excellent performance, can better meet the application requirements of film blowing, blow molding and other applications requiring low melt flow rate, and the prepared product has better performance.

[0042] According to the present invention, in some preferred embodiments, the structure of the polyglycolic acid graft copolymer is as shown in formula (II):

[0043]

[0044] In formula (II), x, y1, y2, p and z all represent the degree of polymerization, wherein x and p are positive integers, y1, y2 and z are all natural numbers; and / or the sum of x, y1, y2 and z is not less than 50, preferably 50 to 6000, more preferably 200 to 2500; and / or p is not less than 50, preferably 70 to 2000.

[0045] According to the present invention, in some embodiments, the low molecular weight portion is a polyglycolic acid homopolymer; preferably, the structure of the polyglycolic acid homopolymer is as shown in formula (III):

[0046]

[0047] In formula (III), n1, ..., n i is the degree of polymerization; i is directly connected to R The number of, i ≥ 1; M i is an imino group, a secondary amino group or an ether bond; R is at least one of hydrogen, an aliphatic group or an aromatic group; when i>1, M1, M2, ..., M i Different or the same between n1, n2, ..., n i are different or the same; preferably, i is any integer between 1 and 20, and the preferred range of i is 2 to 6; the sum of all n values ​​is not less than 100; R is an alkane group or an aromatic hydrocarbon group with a molecular weight of 14 to 1000 g / mol.

[0048] According to the present invention, in some embodiments, the high molecular weight portion is a polyglycolic acid graft copolymer. The polyglycolic acid in the above embodiments can better meet the application requirements of film blowing, blow molding, etc. that require a low melt flow rate.

[0049] According to the present invention, as long as the purpose of the present invention can be achieved, the content of the structural unit a and the structural unit b is not particularly limited. In some preferred embodiments, the polyglycolic acid contains 0.001-10 parts by weight of the polyhydroxy polymer structural unit a and 0.001-10 parts by weight of the structural unit b derived from the small molecule initiator relative to 100 parts by weight of the structural unit b derived from the glycolic acid monomer. More preferably, the polyglycolic acid contains 0.01-1 parts by weight of the polyhydroxy polymer structural unit a and 0.01-1 parts by weight of the structural unit from the small molecule initiator relative to 100 parts by weight of the structural unit b from the glycolic acid monomer.

[0050] In the present invention, the inventors have found that certain properties of a polyglycolic acid precursor can be used and solid-phase thickened to obtain polyglycolic acid that can better meet the application requirements of blown film, blow molding, etc. that require a low melt flow rate. The second aspect of the present invention provides a method for preparing the polyglycolic acid of the present invention. The preparation method comprises: (1) in the presence of a catalyst, a mixture A containing a glycolic acid monomer and a polyhydroxy polymer is subjected to a polymerization step to obtain a polyglycolic acid precursor; (2) a mixture B containing a polyglycolic acid precursor is solid-phase thickened to obtain the polyglycolic acid; wherein the melt flow rate MFR1 of the polyglycolic acid precursor is 230℃ / 2.16kg / MFR2 230℃ / 2.16kg The ratio is not less than 1.3; the conditions for solid phase viscosity enhancement include: the time is 0.5 to 12 hours.

[0051] In the present invention, the preparation process of polyglycolic acid is relatively simple, the equipment requirements are relatively low, and the production efficiency is high. Polyglycolic acid with a low melt flow rate can be obtained in a shorter time, thereby better meeting the application requirements of blown film, blow molding, etc. that require a low melt flow rate.

[0052] According to the present invention, as long as the purpose of the present invention can be achieved, the conditions of the solid phase thickening are not particularly limited. In some preferred embodiments, the conditions of the solid phase thickening include: a temperature of 120 to 210° C., preferably 160 to 190° C. The above-mentioned embodiment can achieve the purpose of the present invention while avoiding the degradation of the polyglycolic acid precursor.

[0053] According to the present invention, in some preferred embodiments, the solid phase viscosity enhancement condition includes: the absolute vacuum degree is not greater than 1000 Pa, preferably not greater than 150 Pa. The above embodiment can achieve the purpose of the present invention while avoiding the degradation of the polyglycolic acid precursor.

[0054] According to the present invention, in some preferred embodiments, the solid phase viscosity enhancement conditions include: a time of 2 to 6 hours. The above embodiments can achieve the purpose of the present invention while avoiding the degradation of the polyglycolic acid precursor.

[0055] According to the present invention, as long as the purpose of the present invention can be achieved, the device for solid phase adhesion is not limited. In some embodiments, the solid phase adhesion is carried out in a vacuum rotating drum reactor.

[0056] According to the present invention, during the solid phase viscosity increasing process, the uniformity of heating of the material can be improved by continuously rotating the drum, and preferably the rotation speed of the drum is 3 to 30 rpm.

[0057] According to the present invention, the preparation efficiency is improved and continuous preparation is achieved. The solid phase viscosity enhancement can be carried out in one or more vacuum rotary drum reactors connected in series and / or in parallel. The present invention has no special limitation on this.

[0058] According to the present invention, as long as the purpose of the present invention can be achieved, in the step (1) of preparing polyglycolic acid, the device for melt polymerization is not particularly limited. In some embodiments, in the step (1), the melt polymerization is carried out in a twin-screw extruder.

[0059] In the present invention, the twin-screw extruder can be a conventional structure in the art, such as the HAAKE Eurolab16 desktop parallel co-rotating twin-screw extruder produced by Thermo Fisher, Germany, the ZSK Mcc18 or ZSK 40 co-rotating parallel twin-screw extruder produced by Coperion, Germany, etc. In a preferred embodiment of the present invention, the aspect ratio of the twin-screw extruder is not less than 40.

[0060] According to the present invention, in some preferred embodiments, the reaction temperature in the twin-screw extruder is 120-250°C, preferably 180-230°C.

[0061] According to the present invention, the reaction temperature in the twin-screw extruder refers to the set temperature of the third heating zone and thereafter, starting from the feed port of the twin-screw extruder.

[0062] According to the present invention, in some preferred embodiments, the rotation speed of the twin-screw extruder is 20 to 250 rpm, preferably 50 to 100 rpm.

[0063] According to the present invention, in some preferred embodiments, the residence time of the mixture A in the twin-screw extruder is 0.2 to 15 min, preferably 1 to 8 min.

[0064] According to the present invention, as long as the purpose of the present invention can be achieved, the feeding rate of the mixture A can be selected as needed, for example, 10 to 30 kg / h.

[0065] The residence time of the mixture A in the twin-screw extruder can be tested using methods known in the art, for example, the time from the black masterbatch entering the screw to the darkest color of the material discharged from the die is taken as the residence time.

[0066] According to the present invention, when preparing the polyglycolic acid precursor in step (1), it is also possible to select molding after melt polymerization according to the specific form of the polyglycolic acid precursor, such as extrusion granulation after melt polymerization. In some embodiments, in step (1), the polyglycolic acid precursor is in the form of cylindrical particles.

[0067] According to the present invention, as long as the purpose of the present invention can be achieved, the size of the cylindrical particles is not particularly limited. In some preferred embodiments, the diameter of the cylindrical particles is 1 to 10 mm, preferably 2 to 5 mm.

[0068] According to the present invention, in some preferred embodiments, the length of the cylindrical particles is 1 to 30 mm, preferably 3 to 6 mm.

[0069] According to the present invention, it can be understood that "polyglycolic acid precursor" refers to polyglycolic acid that is different from the polyglycolic acid described in the present invention obtained after the solid phase viscosity increasing step in parameters such as melt mass flow rate (MFR value), degree of polymerization, molecular weight, and residual monomer content. When the polyglycolic acid described in the present invention has a bimodal distribution of high and low molecular weights, the polyglycolic acid precursor also has a bimodal distribution of high and low molecular weights.

[0070] According to the present invention, after step (1) is completed, step (2) may be performed immediately or not. In some embodiments, the polyglycolic acid precursor obtained in step (1) is stored for a certain period of time before performing step (2), and the preferred storage conditions include: vacuum packaging and low temperature (<0°C, preferably -30 to -10°C) storage for no more than 180 days.

[0071] According to the present invention, in some embodiments, the polyglycolic acid precursor obtained in step (1) is directly subjected to step (2).

[0072] According to the present invention, it is understood that multiple batches of polyglycolic acid precursors can be prepared as needed, and then the prepared polyglycolic acid precursors are mixed (for example, mixed in a mixing bin) before performing step (2).

[0073] According to the present invention, it can be understood that the glycolic acid monomer is a monomer that provides a glycolic acid structural unit. As long as the purpose of the present invention can be achieved, the specific selection of the glycolic acid monomer is not particularly limited. In some embodiments, the glycolic acid monomer is selected from at least one of glycolide, methyl glycolate and glycolic acid.

[0074] According to the present invention, as long as the purpose of the present invention can be achieved, the type of the catalyst is not particularly limited. In some embodiments, the catalyst is selected from transition metal elements, Group IIA metal elements, Group IIIA metal elements, Group IVA metal elements, Group VA metal elements corresponding to at least one salt compound, and / or an organic guanidine catalyst, preferably a salt compound corresponding to at least one of Sn, Bi, Mg, Al, Ca, Fe, Mn, Ti and Zn, and more preferably a Sn salt.

[0075] According to the present invention, the mixture A may further include one or more of a small molecule co-initiator, an antioxidant, an anti-hydrolysis agent, a lubricant, an antistatic agent, a light stabilizer and a brightener as required.

[0076] According to the present invention, the mixture A may further contain one or more of an antioxidant, an ester exchange inhibitor, and an anti-hydrolysis agent as required.

[0077] According to the present invention, it is understood that the small molecule initiator provides the structural unit As long as the purpose of the present invention can be achieved, the type of the small molecule co-initiator is not particularly limited. In some embodiments, the small molecule co-initiator includes a compound containing active hydrogen such as a hydroxyl group or an amino group, and a molecular weight of not more than 1000 g / mol, preferably a compound having a boiling point of not less than 180°C at normal pressure, including but not limited to: ethylene glycol, butanediol, propylene glycol, serinol, leucinol, pentaerythritol, sorbitol, xylitol, amino acids, phenol, hydroquinone, resorcinol, benzyl alcohol, aniline, benzylamine, p-phenylenediamine, m-phenylenediamine, hexamethylenediamine, dodecanediamine, etc.

[0078] According to the present invention, as long as the purpose of the present invention can be achieved, the type of the antioxidant is not particularly limited. Examples of the antioxidant include hindered phenol antioxidants and / or phosphite antioxidants, including but not limited to 2,6-di-tert-butyl-p-cresol, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 2,2'-methylenebis(6-tert-butyl-4-methylphenol), hexanediol bis[β-(3,5-dibutyl-4-hydroxyphenyl)propionate], pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (such as BASF's antioxidant Irganox®). 1010), N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine (such as antioxidant 1024), N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine (such as antioxidant 1098), β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (such as BASF's antioxidant Irganox 1076), 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, triphenyl phosphite, tri(4-nonylphenyl) phosphite, diphenyl isooctyl phosphite, diphenyl isodecyl phosphite, diphenyl di(2-ethylhexyl) phosphite, phenyl diisodecyl phosphite, tri(2-ethylhexyl) phosphite, triisodecyl phosphite, tri(dodecyl) phosphite, pentaerythritol diisodecyl phosphite, tris[2.4-di-tert-butylphenyl] phosphite (such as antioxidant 168), bis(2,4-dicumylphenyl) pentaerythritol diphosphite (such as antioxidant 686) and bis(2,4-di-tert-butylphenyl) propionate] pentaerythritol diphosphite (such as antioxidant 626).

[0079] According to the present invention, as long as the purpose of the present invention can be achieved, the specific type of the anti-hydrolysis agent is not particularly limited, for example, it is at least one of a carbodiimide compound, an oxazoline compound and an epoxy compound, preferably a carbodiimide compound. In the embodiments of the present invention, the anti-hydrolysis agent S9000 is used as an example to illustrate the advantages of the present invention, but the present invention is not limited to this.

[0080] According to the present invention, as long as the purpose of the present invention can be achieved, in step (1), the amount of the catalyst used is not particularly limited. In some embodiments, the amount of the catalyst used is 0.005 to 1 part by mass, preferably 0.01 to 0.1 part by mass, relative to 100 parts by mass of glycolide.

[0081] According to the present invention, as long as the purpose of the present invention can be achieved, in step (1), the amount of the polyhydroxy polymer is not particularly limited. In some embodiments, the amount of the polyhydroxy polymer is 0 to 0.5 parts by mass, preferably 0.005 to 0.1 parts by mass, relative to 100 parts by mass of glycolide.

[0082] According to the present invention, when the mixture A contains a small molecule co-initiator, as long as the purpose of the present invention can be achieved, the amount of the small molecule co-initiator is not limited. For example, relative to 100 parts by mass of glycolide, the amount of the small molecule co-initiator is 0 to 0.5 parts by mass, preferably 0.005 to 0.1 parts by mass.

[0083] According to the present invention, when the mixture A contains an antioxidant, the amount of the antioxidant is not particularly limited as long as the purpose of the present invention can be achieved. For example, relative to 100 parts by mass of glycolide, the amount of the antioxidant is 0 to 2 parts by mass, preferably 0.1 to 1.0 parts by mass.

[0084] According to the present invention, when the mixture A contains an anti-hydrolysis agent, as long as the purpose of the present invention can be achieved, the amount of the anti-hydrolysis agent is not particularly limited. For example, relative to 100 parts by mass of glycolide, the amount of the anti-hydrolysis agent is 0 to 5 parts by mass, preferably 0.3 to 1.0 parts by mass.

[0085] The third aspect of the present invention provides use of the polyglycolic acid of the present invention in blown film products and / or blow molded products.

[0086] In the present invention, the polyglycolic acid of the present invention can be used to prepare blown film products and / or blow molded products using methods and equipment known in the art. The polyglycolic acid of the present invention can better meet the application requirements of blown film, blow molding, etc. that require a low melt flow rate, and the prepared film products have good performance.

[0087] The present invention will be described in detail below through examples. In the following examples, the raw materials are all commercially available products. Glycolide (GL) was purchased from Suzhou Qihang Biotechnology Co., Ltd. with a purity of ≥99.9%; stannous octoate and 1,4-butanediol were purchased from Sinopharm Chemical Reagent Co., Ltd., with a purity of AR grade and a purity of CP grade for stannous octoate; antioxidant 1010 (tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester) was purchased from BASF (China) Co., Ltd., antioxidant 608 (bis(2,4-dicumylphenyl)pentaerythritol di(phosphite) ester) and carbodiimide anti-hydrolysis agent S9000 (poly[nitromethane tetranitro[2,4,6-tri(1-methylethyl)-1,3-phenylene) were purchased from Shanghai Puzhan Industrial Co., Ltd.; ethylene-vinyl alcohol copolymer (EVOH) was purchased from Kuraray Co., Ltd. of Japan with a brand name of EVALTM H171B, ethylene content is 38 mol%; melt flow rate at 190 ° C / 2.16 kg is 1.7 g / 10 min. Polyvinyl alcohol (PVA) was purchased from Chongqing Chuanwei Chemical Co., Ltd. of Sinopec Group, with a brand number of 0588, a degree of polymerization of 500, and a degree of alcoholysis of 88%. Corn starch was purchased from Aladdin Reagent (Shanghai) Co., Ltd., reagent grade, with a weight average molecular weight of about 12400 g / mol;

[0088] In the following examples and comparative examples:

[0089] Figure 1 GPC curves of some examples (Examples 1-3) and comparative examples (Comparative Examples 1-2);

[0090] Figure 2 The influence curves of the number average molecular weight and weight average molecular weight of the high molecular weight portion of polyglycolic acid during the solid phase viscosity enhancement and devolatilization process in Examples 1-3;

[0091] Figure 3 The influence curve of the number average molecular weight and weight average molecular weight of the medium and low molecular weight parts of polyglycolic acid in the process of solid phase viscosity enhancement and devolatilization in Examples 1-3;

[0092] Figure 4 This is the influence curve of the proportion of high molecular weight components in polyglycolic acid during the solid phase viscosity increasing and devolatilization process in Examples 1-3.

[0093] The present invention performs performance measurement according to the following method:

[0094] Gel Permeation Chromatography (GPC): The test instrument was PL-GPC50 gel permeation chromatograph from Angilent, USA, and the processing software was GPC offline. During the test, the mobile phase was hexafluoroisopropanol containing 5mmol / L sodium trifluoroacetate, the flow rate was 1mL / min, the column temperature was 40℃, the injection volume was 100μL, the standard sample was PMMA, and the sample concentration was 1mg / mL.

[0095] Melt flow rate measurement: The test was conducted on a CEAST MF20 melt flow rate tester from Instron, USA. The test temperature was 230°C, the load weight was 2.16 kg, and the preheating time was 4 minutes.

[0096] Residual monomer content test: about 0.04g of sample is dissolved in about 50g of dimethyl sulfoxide at 160℃ until the sample is dissolved, cooled to room temperature, centrifuged and filtered, 1.5μL of the solution is measured and injected into a gas chromatograph for measurement. The value obtained from the measurement is used to calculate the residual monomer content in the form of polymer total content%. Gas chromatography (GC) analysis is performed on Agilent's GC7890 gas chromatograph; the detector is FID; the temperature of the injection port and detector is 300℃; the chromatographic column is DB-FFAP 30m; the vaporization chamber temperature is 200℃; the chromatographic column temperature: the initial temperature is 160℃, and it is increased to 220℃ at a rate of 10℃ per minute and maintained for 4.5min.

[0097] Melt strength and melt fracture energy test: The test was conducted on the Rosand RH7 high pressure capillary rheometer of Malvern Panalytical, China, with the model number of Haul Off (diameter: 2.0mm, length: 20mm), the barrel push rod pressing speed of 15mm / min, the test temperature of 235℃, the initial drawing speed of 3mm / min, the final drawing speed of 50mm / min, and the acceleration time of 3min. Assuming that the time required for melt fracture is 0.1s, the melt fracture energy (unit: J) = melt strength at melt fracture (unit: N) * drawing rate at melt fracture (unit: m / s) * time required for melt fracture (0.1s).

[0098] Example 1

[0099] Preparation of polyglycolic acid precursor: glycolide (GL), stannous octoate, ethylene-vinyl alcohol copolymer (EVOH), 1,4-butanediol, antioxidant 1010, antioxidant 608 and anti-hydrolysis agent S9000 were uniformly mixed in a mass ratio of 100:0.04:0.02:0.03:0.3:0.3:0.5, and then extruded and granulated using a Coya parallel co-rotating twin-screw extruder (screw diameter: 50 mm, aspect ratio: 56) to obtain a polyglycolic acid precursor (diameter of about 3 mm, length of about 6 mm). The extruder has 14 sections from the feed port to the die, of which the first section only serves to feed and cannot be heated. The temperatures of the second to thirteenth sections and the die are set to 50°C, 150°C, 195°C, 195°C, 195°C, 195°C, 195°C, 195°C, 210°C, 210°C, 210°C, and 210°C, respectively. The screw speed is 60 rpm, the feed rate is 20 kg / h, and the residence time is about 6 min. The melt flow rate of the obtained polyglycolic acid precursor (i.e., MFR1 before solid phase viscosity enhancement) is 11.8 g / 10 min.

[0100] Preparation of polyglycolic acid: The obtained polyglycolic acid precursor was vacuum-packed and stored at low temperature (-16°C) for 21 days. After the particles returned to room temperature, they were added to a vacuum rotary drum reactor (DKT 25, GHS Vacuum Technology Co., Ltd., Germany) for solid phase viscosity enhancement at a rotation speed of 7 rpm. At the same time, vacuum devolatilization was performed to obtain polyglycolic acid. The set temperature was 180°C, the absolute vacuum degree was 130 Pa, and the solid phase viscosity enhancement time was 1 hour. The melt flow rate of polyglycolic acid (i.e., MFR2 after solid phase viscosity enhancement) was 2.83 g / 10 min; MFR1 / MFR2 was 4.17. The molecular weight of polyglycolic acid was characterized by GPC (gel permeation chromatography). The characterization results are shown in Tables 1 and Figure 2-4 As shown, the GPC curve of polyglycolic acid is as follows Figure 1 The residual monomer content of polyglycolic acid is 2.69%.

[0101] Example 2

[0102] The method of Example 1 is followed, except that the absolute vacuum degree of solid phase thickening is 80 Pa and the solid phase thickening time is 3 hours; the rest is the same as Example 1.

[0103] The melt flow rate of the polyglycolic acid precursor (ie, MFR1 before solid phase thickening) is 11.8 g / 10 min; the melt flow rate of the polyglycolic acid (ie, MFR2 after solid phase thickening) is 3.18 g / 10 min; and MFR1 / MFR2 is 3.71.

[0104] The molecular weight of polyglycolic acid was characterized by GPC (gel permeation chromatography). The characterization results are shown in Table 1 and Figure 2-4 As shown, the GPC curve of polyglycolic acid is as follows Figure 1The residual monomer content of polyglycolic acid is 2.15%.

[0105] Example 3

[0106] The method of Example 1 is followed, except that the absolute vacuum degree of solid phase thickening is 39 Pa and the solid phase thickening time is 5 hours; the rest is the same as Example 1.

[0107] The melt flow rate of the polyglycolic acid precursor (ie, MFR1 before solid phase thickening) is 11.8 g / 10 min; the melt flow rate of the polyglycolic acid (ie, MFR2 after solid phase thickening) is 2.34 g / 10 min; and MFR1 / MFR2 is 5.04.

[0108] The molecular weight of polyglycolic acid was characterized by GPC (gel permeation chromatography). The characterization results are shown in Table 1 and Figure 2-4 As shown, the GPC curve of polyglycolic acid is as follows Figure 1 The residual monomer content of polyglycolic acid is 3.34%.

[0109] Example 4

[0110] Preparation of polyglycolic acid precursor: Glycolide (GL), stannous octoate, polyvinyl alcohol, 1,4-butanediol, antioxidant 1010, antioxidant 608 and anti-hydrolysis agent S9000 were uniformly mixed in a mass ratio of 100:0.03:0.02:0.03:0.3:0.3:0.5, and then extruded and granulated using a Coya parallel co-rotating twin-screw extruder (screw diameter: 50 mm, aspect ratio: 56) to obtain a polyglycolic acid precursor (diameter of about 3 mm, length of about 6 mm). The extruder has 14 sections from the feed port to the die, of which the first section only serves to feed and cannot be heated, and the temperatures of the second to thirteenth sections and the die are set to 50°C, 150°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 200°C, 210°C, 220°C, 225°C and 225°C, respectively. The screw speed is 60rpm, the feed rate is 20kg / h; the melt flow rate of the obtained polyglycolic acid precursor particles after cooling to room temperature (i.e., MFR1 before solid phase viscosity enhancement) is 4.49g / 10min, and the residence time is about 6min.

[0111] Preparation of polyglycolic acid: After the obtained polyglycolic acid precursor particles are cooled to room temperature, they are immediately added to a vacuum rotary drum reactor (DKT 25, GHS Vacuum Technology Co., Ltd., Germany) for solid phase viscosity enhancement at a rotation speed of 7 rpm. At the same time, vacuum devolatilization is performed to obtain polyglycolic acid. The set temperature is 180°C, the absolute vacuum degree is 45 Pa, and the solid phase viscosity enhancement time is 4 hours.

[0112] The melt flow rate of polyglycolic acid (ie, MFR2 after solid phase viscosity enhancement) is 0.86 g / 10 min; MFR1 / MFR2 is 5.12.

[0113] The residual monomer content of polyglycolic acid is 1.49%.

[0114] Example 5

[0115] Preparation of polyglycolic acid precursor: The method was as described in Example 1, except that EVOH was replaced with corn starch. The melt flow rate of the obtained polyglycolic acid precursor particles after cooling to room temperature (ie, MFR1 before solid phase thickening) was 12.01 g / 10 min.

[0116] Preparation of polyglycolic acid: According to Example 1, the difference is that the actual absolute vacuum is 100 Pa and the solid phase viscosity enhancement time is 3 hours.

[0117] The melt flow rate of polyglycolic acid (i.e., MFR2 after solid phase viscosity enhancement) is 4.26 g / 10 min, MFR1 / MFR2 is 2.82, and the residual monomer content of polyglycolic acid is 3.45%.

[0118] Example 6

[0119] Preparation of polyglycolic acid precursor: According to Example 4, the difference is that the ratio of glycolide (GL), stannous octoate, polyvinyl alcohol, 1,4-butanediol, antioxidant 1010, antioxidant 608 and anti-hydrolysis agent S9000 is changed to 100:0.03:0.005:0.045:0.3:0.3:0.5, and the screw speed and feeding speed are reduced to 50rpm and 15kg / h respectively, and the residence time is about 9min. The melt flow rate (i.e., MFR1 before solid phase viscosity enhancement) of the obtained polyglycolic acid precursor particles after cooling to room temperature is 16.36g / 10min.

[0120] Preparation of polyglycolic acid: According to Example 1, the difference is that the absolute vacuum degree is 110 Pa and the solid phase viscosity enhancement time is 4 hours.

[0121] The melt flow rate of polyglycolic acid (i.e., MFR2 after solid phase viscosity enhancement) is 9.87 g / 10 min, MFR1 / MFR2 is 1.65, and the residual monomer content of polyglycolic acid is 2.34%.

[0122] Comparative Example 1

[0123] The method of Example 1 is followed, except that the absolute vacuum degree is 110 Pa and the solid phase viscosity enhancement time is 18 h; the rest is the same as Example 1.

[0124] The melt flow rate of the polyglycolic acid precursor (i.e., MFR1 before solid phase viscosity enhancement) is 11.8 g / 10 min; the melt flow rate of polyglycolic acid (i.e., MFR2 after solid phase viscosity enhancement) is 10.9 g / 10 min; and MFR1 / MFR2 is 1.08.

[0125] The molecular weight of polyglycolic acid was characterized by GPC (gel permeation chromatography). The characterization results are shown in Table 1 and Figure 2-4 As shown, the GPC curve of polyglycolic acid is as follows Figure 1 The residual monomer content of polyglycolic acid is 3.70%.

[0126] Comparative Example 2

[0127] The polyglycolic acid precursor in Example 1 was used as the polyglycolic acid.

[0128] The melt flow rate of the polyglycolic acid precursor is 11.8 g / 10 min. The GPC curve of polyglycolic acid is as follows: Figure 1 shown.

[0129] Comparative Example 3

[0130] Preparation of polyglycolic acid precursor: The method of Example 1 is followed, except that EVOH is not added, that is, the ratio of glycolide (GL), stannous octoate, 1,4-butanediol, antioxidant 1010, antioxidant 608 and anti-hydrolysis agent S9000 is changed to 100:0.02:0.03:0.3:0.3:0.5, and the rest is the same as Example 1. The melt flow rate of the polyglycolic acid precursor (i.e., MFR1 before solid phase viscosity enhancement) is 35.67 g / 10 min.

[0131] Preparation of polyglycolic acid: The same as in Example 1, the melt flow rate of polyglycolic acid (ie, MFR2 after solid phase viscosity enhancement) was 29.32 g / 10 min; MFR1 / MFR2 was 1.22.

[0132] The molecular weight of polyglycolic acid was characterized by GPC (gel permeation chromatography). The characterization results are shown in Table 1.

[0133] The residual monomer content of polyglycolic acid is 2.95%.

[0134] Comparative Example 4

[0135] The polyglycolic acid precursor in Example 4 was used as the polyglycolic acid.

[0136] The melt flow rate of the polyglycolic acid precursor was 4.49 g / 10 min.

[0137] Comparative Example 5

[0138] The polyglycolic acid precursor in Example 5 was used as the polyglycolic acid.

[0139] The melt flow rate of the polyglycolic acid precursor was 12.01 g / 10 min.

[0140] Comparative Example 6

[0141] The polyglycolic acid precursor in Example 6 was used as the polyglycolic acid.

[0142] The melt flow rate of the polyglycolic acid precursor was 16.36 g / 10 min.

[0143] Table 1

[0144]

[0145]

[0146] Test example

[0147] Melt strength and melt fracture energy can be used to characterize the processability of the polymer for direct blow molding at this temperature. The higher the melt strength and melt fracture energy, the better the processability. Therefore, melt strength and melt fracture energy were tested for each embodiment and comparative example, respectively, at a test temperature of 235°C, and the results are shown in Table 2.

[0148] Table 2

[0149] Melt Strength(cN) Melt fracture energy (mJ) Example 1 24 2.4 Example 2 20 2.6 Example 3 26 2.6 Example 4 92 3.2 Example 5 9.0 1.8 Example 6 2.0 1.0 Comparative Example 1 1.3 0.6 Comparative Example 2 10 2.1 Comparative Example 3 0.1 0.01 Comparative Example 4 11 2.0 Comparative Example 5 1.5 0.8 Comparative Example 6 0.5 0.3

[0150] As can be seen from Table 2, compared with the corresponding comparative examples (Comparative example 2 for the corresponding comparative example of Examples 1 to 3, Comparative example 4 for the corresponding comparative example of Example 4, Comparative example 5 for the corresponding comparative example of Example 5, and Comparative example 6 for the corresponding comparative example of Example 6), the melt strength and melt fracture energy of Examples 1 to 6 are significantly improved, that is, the blow molding processability at this temperature is significantly improved. In addition, as can be seen from Example 1 and Comparative Example 3, the structural unit a derived from the polyhydroxy polymer contained in the polyglycolic acid significantly improves the melt strength and melt fracture energy of the polyglycolic acid (by about 2 orders of magnitude).

[0151] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A polyglycolic acid, characterized in that The polyglycolic acid contains a structural unit a derived from a polyhydroxy polymer; the polyglycolic acid has: Melt flow rate MFR2 230℃ / 2.16kg Not more than 15g / 10min; Melt flow rate MFR1 of polyglycolic acid before and after solid phase thickening 230℃ / 2.16kg / MFR2 230℃ / 2.16kg The ratio is not less than 1.3; MFR1 230℃ / 2.16kg and MFR2 230℃ / 2.16kg They represent the melt flow rates of polyglycolic acid before and after solid phase thickening when tested at 230°C and 2.16 kg.

2. The polyglycolic acid according to claim 1, characterized in that: MFR2 230℃ / 2.16kg Not more than 10 g / 10 min, preferably 0.5 to 5.0 g / 10 min; and / or MFR1 230℃ / 2.16kg / MFR2 230℃ / 2.16kg The ratio is not less than 1.5, preferably 3.0 to 6.0; and / or MFR1 230℃ / 2.16kg It is 3 to 60 g / 10 min, preferably 10 to 40 g / 10 min.

3. The polyglycolic acid according to claim 1 or 2, characterized in that: The average number of hydroxyl groups on a single molecular chain of the polyhydroxy polymer is not less than 8, preferably not less than 20, preferably 100 to 2000; and / or The number average molecular weight of the polyhydroxy polymer is not less than 3000 g / mol, preferably not less than 10,000 g / mol, more preferably 30,000 g / mol to 300,000 g / mol; and / or The polyhydroxy polymer includes at least one of polysaccharides and their derivatives, multi-arm polyethylene oxide, multi-arm polypropylene oxide, multi-arm polyethylene glycol, polyvinyl alcohol and their derivatives, preferably polyvinyl alcohol and / or ethylene-vinyl alcohol copolymer; Preferably, the structure of the structural unit a is as shown in (I): In formula (I), x, y and z all represent the degree of polymerization, the sum of x, y and z is not less than 50, preferably 50-6000, more preferably 200-2500; and / or, the proportion of z to the sum of x+y+z is 0%-50%; and / or, the proportion of x to the sum of x+y is 0%-32%.

4. The polyglycolic acid according to claim 3, characterized in that: The residual monomer content of the polyglycolic acid is not higher than 3.5% by mass, preferably 0.1% to 2.5%; and / or The total weight average molecular weight of the polyglycolic acid is 200,000 to 600,000 g / mol; and / or The polyglycolic acid comprises a low molecular weight portion and a high molecular weight portion, and preferably the mass ratio of the high molecular weight portion to the low molecular weight portion is 1:200 to 3:2, preferably 2:98 to 60:40; Preferably, The weight average molecular weight of the high molecular weight part of the polyglycolic acid is greater than 500,000 g / mol, preferably 2.5 million g / mol to 4 million g / mol; and / or The weight average molecular weight of the low molecular weight part of the polyglycolic acid is 150,000 g / mol to 300,000 g / mol; and / or The content of oligomers with a weight average molecular weight of less than 10000 g / mol in the polyglycolic acid is less than 0.5% by mass.

5. The polyglycolic acid according to claim 4, characterized in that: The high molecular weight portion is a polyglycolic acid graft copolymer, and preferably the polyglycolic acid graft copolymer contains a structural unit a and a structural unit b derived from a glycolic acid monomer; Preferably, the structure of the polyglycolic acid graft copolymer is as shown in formula (II): In formula (II), x, y1, y2, p and z all represent the degree of polymerization, wherein x and p are positive integers, y1, y2 and z are all natural numbers; and / or the sum of x, y1, y2 and z is not less than 50, preferably 50 to 6000, more preferably 200 to 2500; and / or p is not less than 50, preferably 70 to 2000.

6. The polyglycolic acid according to claim 4 or 5, characterized in that: The low molecular weight portion is a polyglycolic acid homopolymer; Preferably, the structure of the polyglycolic acid homopolymer is as shown in formula (III): In formula (III), n1, ..., n i is the degree of polymerization; i is directly connected to R The number of, i ≥ 1; M i is an imino group, a secondary amino group or an ether bond; R is at least one of hydrogen, an aliphatic group or an aromatic group; when i>1, M1, M2, ..., M i Different or the same between n1, n2, ..., n i different or the same between them; More preferably, i is any integer between 1 and 20, and the preferred range of i is 2 to 6; all n1, ..., n i The sum of the values ​​is not less than 100; R is an alkane group or an aromatic hydrocarbon group with a molecular weight of 14 to 1000 g / mol.

7. The polyglycolic acid according to claim 6, characterized in that: The polyglycolic acid contains 0.001-10 parts by weight of the polyhydroxy polymer structural unit a and 0.001-10 parts by weight of the structural unit derived from the small molecule initiator relative to 100 parts by weight of the structural unit b derived from the glycolic acid monomer. Preferably, the polyglycolic acid contains 0.01-1 parts by mass of the polyhydroxy polymer structural unit a and 0.01-1 parts by mass of the structural unit from the small molecule initiator relative to 100 parts by mass of the structural unit b from the glycolic acid monomer.

8. A method for preparing the polyglycolic acid according to any one of claims 1 to 7, characterized in that: The preparation method comprises: (1) in the presence of a catalyst, subjecting a mixture A comprising a glycolic acid monomer and a polyhydroxy polymer to a step including melt polymerization to obtain a polyglycolic acid precursor; (2) solid phase thickening of the mixture B containing the polyglycolic acid precursor to obtain the polyglycolic acid; Among them, the melt flow rate MFR1 of the polyglycolic acid precursor 230℃ / 2.16kg / MFR2 230℃ / 2.16kg The ratio is not less than 1.3; The conditions for the solid phase thickening include: a time of 0.5 to 12 hours.

9. The preparation method according to claim 8, characterized in that: The conditions for the solid phase viscosity enhancement include: The temperature is 120-210°C, preferably 160-190°C; and / or The absolute vacuum degree is not greater than 1000 Pa, preferably not greater than 150 Pa; and / or Duration is 2 to 6 hours; and / or The solid phase adhesion is carried out in a vacuum rotating drum reactor.

10. The preparation method according to claim 8 or 9, characterized in that: In step (1), the melt polymerization is carried out in a twin-screw extruder; Preferably, the reaction temperature in the twin-screw extruder is 120 to 250° C., preferably 180 to 230° C.; and / or The rotation speed of the twin-screw extruder is 20 to 250 rpm, preferably 50 to 100 rpm; and / or The residence time of the mixture A in the twin-screw extruder is 0.2 to 15 minutes, preferably 1 to 8 minutes.

11. The preparation method according to any one of claims 8 to 10, characterized in that: In step (1), the polyglycolic acid precursor is in the form of cylindrical particles; Preferably, the diameter of the cylindrical particles is 1 to 10 mm, preferably 2 to 5 mm; and / or The length of the cylindrical particles is 1 to 30 mm, preferably 3 to 6 mm.

12. The preparation method according to any one of claims 7 to 11, characterized in that: The glycolic acid monomer is selected from at least one of glycolide, methyl glycolate and glycolic acid; and / or The catalyst is selected from the salt compounds corresponding to at least one of transition metal elements, IIA group metal elements, IIIA group metal elements, IVA group metal elements, and VA group metal elements, and / or organic guanidine catalysts, preferably a salt compound corresponding to at least one of Sn, Bi, Mg, Al, Ca, Fe, Mn, Ti and Zn, more preferably a Sn salt; and / or The mixture A further contains one or more of a small molecule co-initiator, an antioxidant, an anti-hydrolysis agent, a lubricant, an antistatic agent, a light stabilizer and a brightener; and The mixture B further contains one or more of an antioxidant, an ester exchange inhibitor, and an anti-hydrolysis agent; and / or The amount of the catalyst is 0.005 to 1 part by mass, preferably 0.01 to 0.1 part by mass, relative to 100 parts by mass of glycolide; and / or The amount of the polyhydroxy polymer used is 0 to 0.5 parts by mass, preferably 0.005 to 0.1 parts by mass, relative to 100 parts by mass of glycolide.

13. Use of the polyglycolic acid according to any one of claims 1 to 7 in blown film products and / or blow molded products.

Citation Information

Patent Citations

  • Method for adjusting polyglycolic acid molecular chain structure

    CN111647144A

  • Preparation method of granular polyglycolic acid

    CN115505107A

  • Polyglycolic acid resin composition, manufacturing method therefor, and molding thereof

    JP2009040917A

  • Poly(glycolic acid) for containers and films with reduced gas permeability

    US20210198422A1

  • Synthesis of polylactone-grafted evoh

    WO2006097656A1